A Review on Certification Procedure for Professionals Engineer based on Engineering Act in Indonesia - Irika Widiasanti; Rizal Z Tamin (International Conference on Coastal and Delta Areas, 2015)
The coastal area has a very strategic value because the city nearby this area can bedeveloped as a port city, recreation and conservation. Development of coastal areas requires professional human resources. Professional credentials for individuals can be attained through professional certification. This paper presents the procedure of professional certification base on Decree no. 11,2014 on Engineering. This study is a descriptive and qualitative research, carried out through the stages of literature study and data collection include professional competence assurance system, profession licence, qualification assurance systems engineering profession. Data were analyzed reference to best practices certification procedure in Malaysia, Singapore and the Philippines. The study show there are two stages of examinations and three standards in the certification procedure. The examinations are professional examinations and competence examinations. Professional examinations held in the Professional Engineers Program while competence examinations organize byProfessional Certification Body. The standard that used are the Engineers Service Standard, Engineers Competency Standard, and Engineers Professional Program Standard. All of these standards underlying the certification engineering procedure. Institutions directly involved in the certification process are the Board of Engineers Indonesia, Higher Education that organizer Profession Engineers Program, Professional Certification Body, and The Institution of Engineers Indonesia